Pengelolaan kesehatan kulit masyarakat pada masa pandemi Covid-19 di Desa Ranah Kecamatan Kampar - Zahtamal Zahtamal; Tuti Restuastuti; Ridha Restila; Yuni Eka. A; Yusdiana Yusdiana (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2020)
Based on data from the Kampar Health Center, it is known that the high number of skin disease cases suffered by the community, especially during the Covid-19 pandemic in 2020. The purpose of this activity is to empower the community, especially in managing skin health during the Covid-19 pandemic. The method of empowerment: mapping the types of skin diseases in the community during the Covid-19 pandemic, increasing public awareness and understanding of skin disease management and prevention efforts, providing treatment for skin disease sufferers, and strengthening community resources in improving behaviour for prevention and management skin disease. This activity has been carried out by always paying attention to health protocols during the Covid-19 pandemic. The results that have been obtained include increasing public understanding of the importance of maintaining cleanliness and skin health during the Covid-19 period, increasing public awareness and motivation to continue to consult with health workers in health care facilities in dealing with their skin diseases. This activity has also provided benefits to various parties, including the Kampar Health Center, health cadres, regional leaders and community leaders to continue to coordinate and increase public awareness of the importance of skin health.